Beefcaltle mineral nutrition in the Brazilian "Pantanal". V. Macronutrients survey on the Aquidauana subregion - Pott, Edison B.; Brum, Paulo A.R. de; Almeida, Irajá L. de; Filho, José A. Comastri; Pott, Arnildo (Pesquisa Agropecuaria Brasileira, 2014)
Samples of soil, forages and beef cow tissues sampled in November 1982 and May and August 1983 were analysed. Soils and forages were sampled in five landscape units: forest, savanna, high and low Elyonurus grassland and open wet grassland. Soil pH varied from 5.1 to 5.9; Al from 5 to 58 ppm; exchangeable cations: Ca from 104 to 322 ppm; Mg from 17 to 52 ppm; K from 20 to 26 ppm; Na from 2 to 46 ppm; and available P from 1.7 to 3.7 ppm. In the forages, Ca varied from 0.16 to 0.26%; Mg from 0.12 to 0.25%; K from 0.65 to 1.49% and P, from 0.10 to 0.19%. In blood serum, in May and August, the mean levels (mg/100 ml) were: Ca = 9.4 and 8.4; P = 4.2 and 6.0; and Mg = 2.9and 3.1, respectively. In bone (% in ash), Ca varied from 35.4 to 38.6; P from 16.6 to 17.7; and Mg from 0.58 to 0.62. The soils were deficient in Ca, Mg, K and P and the forages, in P. Levels of Ca. Mg and P in animal tissues suggest a possible deficiency of these nutrients in the diet.